Socio-economic problems of modern land system of Russia - Yu. M. Rogatnev; I. S. Ryzhova (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes the results of land reform in terms of land relations and land use. The socio-economic problems that have arisen as a result of it are shown. The assessment of the system of private ownership of land, its impact on rural residents and agricultural production is given. The main problems and trends of changes in the land use system related to the non-delimited state ownership of land, the lack of demand for land shares and the non-use of significant areas of agricultural land are indicated. The changes in the land use system are shown in connection with its new goal — to maximize profits. The necessity of changing the paradigm of land use is justified — the transition from an effective owner of land to its effective user.